La persévérance des professeurs des écoles : étude des effets d’un dispositif d’espace de dons encouragés - Peggy Neville (Recherches en Éducation)
This article focuses on a perseverance support system for school teachers called Encouraged Giving Spaces (EGS). The EGS aim to transform, improve, and better understand the perseverance actions of professionals. In this research, we hypothesized that teacher and student persistence in the classroom emerges from a situated, normative, and relational understanding that is continually self-organizing in action. This article presents the transformations resulting from this device by being part of a research program conducted in culturalist anthropology hybridized with an anti-utilitarian conception of activity developed from the gift paradigm. The results show a transformation of teachers' perseverance actions towards their dropout students in an ordinary work situation and the reflexive development of school teachers through the emergence of fruitful alternative perseverance actions induced by the students' point of view.